The Effectiveness of Quantum Learning Method to Students’ English Learning Achievement at SMK N 9 Padang - Zia Syukria (Universitas Batanghari Jambi, 2019)
This research aimed to find out the effectiveness of Quantum Learning Method to students’ English learning achievement. This research was pre-experimental design in the form of one group Pretest- Posttest. It was conducted at SMK N 9 Padang. The sample of this research was class X Hotel Acomodation 3 with total number of sample was 27. The instrumentation used as a data collection was test. The findings showed the effectiveness of using quantum learning methods which can be seen from the value of learning achievement. The findings of this research; quantum learning method is quite effective to improve students' English learning achievement on the material